Geometrically nonlinear continuum thermomechanics with surface energies coupled to diffusion - McBride, Andrew; Javili, Ali; Steinmann, Paul; Bargmann, Swantje (Journal of the Mechanics and Physics of Solids, 2011)
Surfaces can have a significant influence on the overall response of a continuum body but are often neglected or accounted for in an ad hoc manner. This work is concerned with a nonlinear continuum thermomechanics formulation which accounts for surface structures and includes the effects of diffusion and viscoelasticity. The formulation is presented within a thermodynamically consistent framework and elucidates the nature of the coupling between the various fields, and the surface and the bulk. Conservation principles are used to determine the form of the constitutive relations and the evolution equations. Restrictions on the jump in the temperature and the chemical potential between the surface and the bulk are not a priori assumptions, rather they arise from the reduced dissipation inequality on the surface and are shown to be satisfiable without imposing the standard assumptions of thermal and chemical slavery. The nature of the constitutive relations is made clear via an example wherein the form of the Helmholtz energy is explicitly given. © 2011 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-TM.geomet_1
Keywords: Constitutive behaviour; Diffusion; bulk and surface; Finite strain; Thermomechanical process